Lossless real-time characterization method for strength recovery of cement-based material in self-repairing process
By establishing an exponential relationship model between wave velocity and intensity, and using ultrasonic non-destructive detection technology, the problem that traditional methods cannot monitor the strength of cement-based materials in real time is solved, and high-precision non-destructive strength prediction is achieved, which is suitable for strength recovery evaluation in the self-repair process.
Patent Information
- Application Number
- CN202411858821.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional cement-based materials strength evaluation methods rely on destructive tests, and cannot achieve real-time monitoring and long-term evaluation, making it difficult to effectively evaluate strength recovery during self-repair.
By establishing an exponential relationship model between wave velocity and intensity, using ultrasonic non-destructive detection technology, the wave velocity data of cement-based materials are monitored in real time, and the regression coefficient is optimized through regression analysis to predict the strength recovery of the material.
It realizes high-precision lossless real-time characterization of cement-based material strength, and can quickly and accurately evaluate its strength recovery without destroying the material. It is suitable for large-scale material quality inspection and engineering monitoring.
Smart Images

Figure CN119804656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a performance evaluation method for cement-based materials, and in particular to a non-destructive real-time characterization method for strength recovery during a cement-based material self-repairing process. Background Art
[0002] Self-healing cementitious materials can automatically repair cracks when damaged by external factors, thereby restoring their mechanical properties. Therefore, they have attracted wide attention in the fields of construction and engineering structures. Cementitious materials may be damaged during use, resulting in a decrease in mechanical properties. Self-healing materials partially or completely restore their properties by filling cracks or restoring the original microstructure. Traditional strength assessment methods rely on destructive testing, which requires the destruction of material specimens, making it difficult to achieve real-time monitoring and long-term assessment. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a non-destructive real-time characterization method for strength recovery of cement-based materials during self-healing process with high precision.
[0004] Technical solution: A non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process of the present invention comprises:
[0005] (1) Four groups of cement-based material specimens with repair particles were prepared as the control group. After the specimens were formed, they were cured under standard conditions. When they reached 3d, 7d, 14d, and 28d, the wave velocity and compressive strength of the control group specimens at these four curing ages were measured;
[0006] (2) Establish an exponential relationship model between wave speed and intensity:
[0007]
[0008] Where f is the strength of cement-based materials, MPa; v is the wave velocity, km / s; α1 and α2 are regression coefficients;
[0009] By performing regression analysis on the wave velocity and compressive strength experimental data obtained in step (1), the regression coefficients α1 and α2 are optimized to obtain a strength recovery prediction model suitable for a specific cement-based material;
[0010] (3) Measuring the wave velocity of the specific cement-based material specimen at different repair ages during the self-repair process, and obtaining the corresponding strength according to the strength recovery prediction model.
[0011] Furthermore, in step (1), several groups of cement-based material specimens with repair particles are prepared as self-repairing groups;
[0012] The lossless real-time characterization method further comprises:
[0013] (4) After the self-repairing group specimens reached the curing age of 28 days, they were subjected to different degrees of pre-destruction. The repair process lasted for 28 days. Assuming that the repair age was divided into N stages, the specimens with the same degree of pre-destruction in the self-repairing group were group N+1.
[0014] For specimens with the same pre-destruction degree, one group is selected for wave velocity measurement and compressive destruction until the specimen is completely destroyed to obtain the residual compressive strength of the specimen; the remaining N groups of specimens are self-repaired at different repair ages. After the repair expires, the wave velocity data of the specimens are collected and the corresponding strength is obtained according to the strength recovery prediction model; after the wave velocity measurement is completed, the compressive strength is destroyed to obtain its actual compressive strength;
[0015] The same operation was performed on the specimens with other pre-destruction degrees;
[0016] (5) The accuracy of strength recovery prediction is evaluated using the strength recovery rate and ultrasonic non-destructive characterization accuracy.
[0017] Furthermore, the strength recovery rate calculation formula is:
[0018]
[0019] Where, S is the strength recovery rate of the specimen; E i is the actual compressive strength of the specimen at different repair ages, and E0 is the residual compressive strength of the specimen, MPa.
[0020] Furthermore, the calculation formula for the accuracy of ultrasonic non-destructive characterization is:
[0021]
[0022] Where η is the accuracy of ultrasonic non-destructive characterization; E ij is the predicted strength of the specimen, MPa.
[0023] Furthermore, the specimen is a standard cubic specimen.
[0024] Furthermore, the pre-destruction of the specimen is achieved by maintaining the load for a certain period of time.
[0025] Furthermore, different degrees of pre-destruction were set to 60% and 80% of the standard compressive strength at 28d, where the load was held for 60s at 60% load and for 20s at 80% load.
[0026] Furthermore, the self-repair process of the specimen is achieved by placing it in an artificial simulated seawater solution.
[0027] Furthermore, the chemical components of the artificial simulated seawater solution include NaCl, MgCl2, Na2SO4, CaCl2, and KCl, and the corresponding concentrations are 24.5-25.5 g / L, 4.0-5.0 g / L, 4.0-4.5 g / L, 1.1-1.2 g / L, and 0.6-0.7 g / L, respectively.
[0028] Furthermore, ultrasonic testing was performed at different positions of the cement-based material specimens. The normal ultrasonic waveform was a sine wave. When the collected ultrasonic waveform was chaotic, it was judged to be affected by noise or improper coupling of the measuring equipment. The data with chaotic waveforms were removed and remeasured.
[0029] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0030] (1) High-precision non-destructive strength prediction: By establishing an exponential fitting relationship between ultrasonic wave velocity and cement-based material strength, the strength prediction of the self-healing cement-based material strength recovery process is realized. This method can accurately evaluate the strength of cement-based materials without destroying the materials, and is suitable for large-scale material quality testing and engineering monitoring.
[0031] (2) Fast and efficient: This method can quickly obtain the wave velocity data of the material and predict the strength of the material through a simple regression model, which is suitable for real-time monitoring and quality control.
[0032] (3) Wide applicability: This method is not only applicable to cement-based materials of C30 and M20 strength grades, but can also be extended to cement-based materials of other strength grades, and has strong versatility.
[0033] The present invention can provide a scientific evaluation basis for the strength recovery process of self-repairing cement-based materials, and can be widely used in the maintenance and repair of engineering structures, providing technical support for ensuring the safety and durability of the structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a wave velocity-strength fitting curve diagram of the C30 concrete material in Example 1 of the present invention;
[0035] Figure 2 is a bar graph of the strength recovery rate of the C30 concrete material in Example 1 of the present invention;
[0036] Figure 3 is a comparison diagram of the calculated strength and actual strength errors of the C30 concrete material in Example 1 of the present invention;
[0037] Figure 4 is a wave velocity-strength fitting curve diagram of the M20 cement mortar material in Example 2 of the present invention;
[0038] Figure 5 is a bar graph of the strength recovery rate of the M20 cement mortar material in Example 2 of the present invention;
[0039] Figure 6 It is a comparison diagram of the calculated strength and actual strength errors of the M20 cement mortar material in Example 2 of the present invention. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings.
[0041] According to different application environments, C30 concrete is the most commonly used concrete strength grade, suitable for medium and high-rise buildings, general bridges and underground projects, etc. M20 mortar is also a commonly used mortar strength grade, mainly used for buildings and foundation construction with high strength requirements, suitable for walls and foundations with high strength requirements, and often used in load-bearing walls, columns, floor slabs, and bridge structures. Therefore, C30 concrete grade and M20 mortar strength grade were selected for the test of self-repairing cement-based materials.
[0042] Example 1
[0043] This Example 1 uses standard concrete cube specimens with a strength grade of C30, and the repair particles are mixed with cement with a mass fraction of 6%. All specimens are cured under standard laboratory conditions. In the experiment, 10 groups of concrete cube specimens with a size of 100mm×100mm×100mm are set, with 3 specimens in each group. The experiment is divided into two groups, 4 groups as the control group and 6 groups as the self-repair group.
[0044] During the standard curing process, the control group specimens were subjected to ultrasonic velocity and compressive strength tests at 3d, 7d, 14d, and 28d. The fitting curves of wave velocity and strength were drawn based on the obtained data, as shown in Figure 1 shown.
[0045] f=(0.12229±0.03113)×e (1.21288±0.05666)v
[0046] Among them, R 2 The value is 0.980, with a high degree of fit, which effectively reflects the strength of concrete materials. 2 It is the correlation coefficient of the fitting curve, which is automatically calculated by the origin software and is used to measure the degree of fitting. The closer it is to 1, the better the degree of fitting.
[0047] The remaining 6 groups are self-repair groups. After the specimens are formed, they are cured under standard conditions for 28 days. After the 28-day curing period, different degrees of pre-destruction are carried out by a universal testing machine. Since the standard compressive strength of 35.0 MPa at 28 days is obtained, the pre-destruction is achieved by setting 60% and 80% of the standard compressive strength and maintaining the load for a certain period of time. Then, the load is 21.0 MPa at 60% load, 60s, and 28.0 MPa at 80% load, 20s. Among them, 3 groups of specimens are loaded with 60% load, and the other 3 groups of specimens are loaded with 80%.
[0048] One group of specimens was loaded with 60% and another group was loaded with 80%. The load was reapplied to these two groups of specimens to measure the wave velocity and compressive failure, and the residual compressive strength was obtained to be 23.3MPa and 18.4MPa.
[0049] For the remaining 4 groups of specimens, they were placed in artificial simulated seawater solution for self-repair, and the repair process lasted for 28 days. The specimens with a repair age of 14d and 28d were tested using an ultrasonic probe with a frequency of 50kHz, and their wave velocity data were collected. Under a load of 60%, the strength was measured to be 28.4MPa and 29.4MPa; under a load of 80%, the strength was measured to be 23.0MPa and 25.4MPa. After each test, the exponential relationship model between wave velocity and strength was used to predict the strength recovery of the material, and the tested specimens were subjected to compressive damage to obtain their actual compressive strength. Under a load of 60%, the recovery wave velocities of 14d and 28d were measured to be 4.460km / s and 4.500km / s, respectively. Through the wave velocity-strength fitting curve, the corresponding strengths were obtained to be 27.5MPa and 28.8MPa. Under 80% load, the recovery wave velocities at 14d and 28d are 4.263km / s and 4.350km / s. Through the wave velocity-intensity fitting curve, the corresponding strengths are obtained to be 21.3MPa and 23.8MPa.
[0050] The test data is processed and calculated according to the above formulas (2) and (3), and the results are as follows: Figure 2 and Figure 3 As shown, the strength repair rate obtained based on the ultrasonic data is evaluated by comparing it with the actual destructive test results.
[0051] Example 2
[0052] This Example 2 uses standard cement mortar cube specimens of M20 strength grade, mixed with repair particles with a cement mass fraction of 6%. All specimens are cured under standard laboratory conditions. In the experiment, 10 groups of cement mortar cube materials with a size of 70.7mm×70.7mm×70.7mm are set, with 3 specimens in each group. The experiment is divided into two groups, 4 groups as the control group and 6 groups as the self-repair group.
[0053] During the standard curing process, the control group specimens were subjected to ultrasonic velocity and compressive strength tests at 3d, 7d, 14d, and 28d. The fitting curves of wave velocity and strength were drawn based on the obtained data, as shown in Figure 4 shown.
[0054] f=(0.20928±0.04556)×e (1.32592±0.06332)v
[0055] Among them, R 2 The value is 0.983, with a high degree of fit, which effectively reflects the strength of cement mortar.
[0056] The remaining 6 groups are self-repair groups. After the specimens are formed, they are cured under standard conditions for 28 days. After the 28-day curing period, different degrees of pre-destruction are carried out by a universal testing machine. Since the standard compressive strength of 23.1 MPa at 28 days is obtained, the pre-destruction is achieved by setting 60% and 80% of the standard compressive strength and maintaining the load for a certain period of time. Then, the load is 13.9 MPa at 60% load, 60s, and 18.5 MPa at 80% load, 20s. Among them, 3 groups of specimens are loaded with 60% load, and the other 3 groups of specimens are loaded with 80%.
[0057] One group of specimens was loaded with 60% and another group was loaded with 80%. The load was reapplied to these two groups of specimens to measure the wave velocity and compressive failure, and the residual compressive strength was obtained to be 16.1MPa and 12.9MPa.
[0058] For the remaining 4 groups of specimens, they were placed in artificial simulated seawater solution for self-repair, and the repair process lasted for 28 days. The specimens with a repair age of 14d and 28d were tested using an ultrasonic probe with a frequency of 50kHz, and their wave velocity data were collected. Under a load of 60%, the strength was measured to be 19.5MPa and 21.8MPa; under a load of 80%, the strength was measured to be 17.5MPa and 21.6MPa. After each test, the exponential relationship model between wave velocity and strength was used to predict the strength recovery of the material, and the tested specimens were subjected to compressive damage to obtain their actual compressive strength. Under a load of 60%, the recovery wave velocities of 14d and 28d were measured to be 3.333km / s and 3.379km / s, respectively. Through the wave velocity-strength fitting curve, the corresponding strengths were obtained to be 17.9MPa and 18.9MPa. Under 80% load, the recovery wave velocities at 14d and 28d are 3.260km / s and 3.307km / s. Through the wave velocity-strength fitting curve, the corresponding strengths are obtained to be 17.5MPa and 17.3MPa.
[0059] The test data is processed and calculated according to the above formulas (2) and (3), and the results are as follows: Figure 5 and Figure 6As shown, the strength repair rate obtained based on the ultrasonic data is evaluated by comparing it with the actual destructive test results.
[0060] The above exponential regression model was used to predict the strength of the specimens in the self-healing process according to Example 1 and Example 2, and compared with the actual destructive test results. The experimental results show that the strength prediction error based on wave velocity is less than 10%, thus verifying the effectiveness and accuracy of the non-destructive characterization method for the strength recovery of self-healing cement-based materials.
Claims
1. A non-destructive real-time characterization method for strength recovery of cement-based materials during self-repair process, characterized in that: include: (1) Four groups of cement-based material specimens with repair particles were prepared as the control group. After the specimens were formed, they were cured under standard conditions. When they reached 3d, 7d, 14d, and 28d, the wave velocity and compressive strength of the control group specimens at these four curing ages were measured; (2) Establish an exponential relationship model between wave speed and intensity: Where f is the strength of cement-based materials, MPa; v is the wave velocity, km / s; α1 and α2 are regression coefficients; By performing regression analysis on the wave velocity and compressive strength experimental data obtained in step (1), the regression coefficients α1 and α2 are optimized to obtain a strength recovery prediction model suitable for a specific cement-based material; (3) Measuring the wave velocity of the specific cement-based material specimen at different repair ages during the self-repair process, and obtaining the corresponding strength according to the strength recovery prediction model.
2. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 1, characterized in that: In step (1), several groups of cement-based material specimens with repair particles are also prepared as a self-repairing group; The lossless real-time characterization method further comprises: (4) After the self-repairing group specimens reached the curing age of 28 days, they were subjected to different degrees of pre-destruction. The repair process lasted for 28 days. Assuming that the repair age was divided into N stages, the specimens with the same degree of pre-destruction in the self-repairing group were group N+1. For specimens with the same pre-destruction degree, one group is selected for wave velocity measurement and compressive destruction until the specimen is completely destroyed to obtain the residual compressive strength of the specimen; the remaining N groups of specimens are self-repaired at different repair ages. After the repair expires, the wave velocity data of the specimens are collected and the corresponding strength is obtained according to the strength recovery prediction model; after the wave velocity measurement is completed, the compressive strength is destroyed to obtain its actual compressive strength; The same operation was performed on the specimens with other pre-destruction degrees; (5) The accuracy of strength recovery prediction is evaluated using the strength recovery rate and ultrasonic non-destructive characterization accuracy.
3. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 2, characterized in that: The strength recovery rate calculation formula is: Where, S is the strength recovery rate of the specimen; E i is the actual compressive strength of the specimen at different repair ages, and E0 is the residual compressive strength of the specimen, MPa.
4. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 3, characterized in that: The calculation formula for the accuracy of ultrasonic non-destructive characterization is: Where η is the accuracy of ultrasonic non-destructive characterization; E ij is the predicted strength of the specimen, MPa.
5. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 2, characterized in that: The specimen is a standard cubic specimen.
6. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 2, characterized in that: The pre-destruction of the specimen is achieved by maintaining the load for a certain period of time.
7. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 6, characterized in that: Different degrees of pre-destruction were set at 60% and 80% of the standard compressive strength at 28d, with the load being held for 60s at 60% and for 20s at 80%.
8. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 2, characterized in that: The self-healing process of the specimen is achieved by placing it in an artificial simulated seawater solution.
9. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 8, characterized in that: The chemical components of the artificial simulated seawater solution include NaCl, MgCl2, Na2SO4, CaCl2, and KCl, with corresponding concentrations of 24.5-25.5 g / L, 4.0-5.0 g / L, 4.0-4.5 g / L, 1.1-1.2 g / L, and 0.6-0.7 g / L, respectively.
10. The non-destructive real-time characterization method for strength recovery of cement-based materials during self-repairing process according to claim 2, characterized in that: Ultrasonic testing was performed at different locations of the cement-based material specimens. When the collected ultrasonic waveform was chaotic, it was judged to be affected by noise or improper coupling of the measuring equipment. The data with chaotic waveforms were removed and remeasured.
Citation Information
Patent Citations
Evaluation method of self-repairing effect of self-repairing cement-based material
CN105300801A
Method for detecting compressive strength of plastic concrete based on ultrasonic waves
CN115980193A